Adipose tissue-derived mesenchymal stem cells cultured at high density express IFN-β and TRAIL and suppress the growth of H460 human lung cancer cells. (January 2019) - Jung, Pil Young; Ryu, Hoon; Rhee, Ki-Jong; Hwang, Soonjae; Lee, Chang Gun; Gwon, Sun-Yeong; Kim, Jiye; Kim, Juwon; Yoo, Byung-Su; Baik, Soon Koo; Bae, Keum Seok; Eom, Young Woo
Abstract: Although mesenchymal stem cells (MSCs) have been reported to inhibit tumor growth, the mechanism controlling this tumor suppression function is unclear. Here, we report that high-density (40, 000 cells/cm 2 ) cultured adipose tissue-derived MSCs (40K-ASCs) expressed interferon (IFN)-β and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL); we also found that serum deprivation during cell culture induced the expression of IFN-β and TRAIL. In addition, the mRNA expression of IFN-β, but not TRAIL, was increased during the washing step required for the transplantation of normal-density (5000 cells/cm 2 ) cultured ASCs (5K-ASCs). When the human lung cancer cell line H460 was co-cultured with 40K-ASCs, necrotic cell death was dramatically increased in vitro . When ASCs were injected after four washes, both 5K-ASCs and 40K-ASCs substantially reduced tumor weight in H460-derived cancer animal models. These results suggest that serum deprivation during the culture of 40K-ASCs or during the washing step of 5K-ASCs can induce IFN-β and/or TRAIL expression, ultimately leading to the tumor suppression capability of ASCs. Highlights: High-density cultured ASCs expressed IFN-β and TRAIL. Serum deprivation induced IFN-β/TRAIL expression in high-density cultured ASCs. IFN-β mRNA expression was increased during washing with phosphate-buffered saline. H460 necroptosis occurred in culture with high-density cultured ASCs. High-density cultured ASCs reduced tumor weight in murine xenograft model.